Generalization of experience in the questions of improving the throwing elements with the hoop of young athletes in rhythmic gymnastics - Alla Semyzorova; Inna Krasova; Kseniia Shevchenko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to summarize coaching experience in improving throwing elements with a hoop for gymnasts 7-8 years old. Material and methods: the study involved one hundred twenty athletes 7-8 years old, training at the Rhythmic Gymnastics School of the city of Kharkov and the city of Szczecin. The level of possession of the throwing movements of the hoop was determined using characteristic motor tests and application video recordings. The assessment of the competitive exercise was carried out by the method expert assessments. The experts were coaches with a referee category in rhythmic gymnastics. The result was determined in accordance with the rules of the competition. The maximum score is 10.0 points. Results: the level of mastery of the basic throwing elements with a hoop was revealed for gymnasts of 7-8 years old, the method of error correction was substantiated. The gymnasts received the lowest marks in the following tests: "Throwing a hoop lying on the floor with a swing of the foot with rotation around the diametrical axis of the apparatus on a sideways turnover, catching a jump through the hoop ( - 6,2 points); «Throw from a spin in the lateral plane with the left hand» ( 7,0 points); «Throw with a swing of a horizontally located hoop, catching in the passage in a sideways flip» ( 7,5 points). Conclusions: the lowest results were obtained when performing the elements of «difficulties», «risks», «skill» and when performing throws with the left hand. The result for performing a competitive exercise with a hoop is 7,2 points. The repeated results of throwing actions with a hoop increased from 7% to 31% and ranged from 8,1 points to 9,5 points. For the performance of a competitive exercise with a hoop, the result increased by 18% and is 8,5 points.